Fabrication of polycaprolactone electrospun nanofibers doped with silver nanoparticles formed by air plasma treatment. (14th March 2019) - Binkley, Dakota M; Lee, Bryan E J; Saem, Sokunthearath; Moran-Mirabal, Jose; Grandfield, Kathryn
Abstract: Implanted devices are prone to bacterial infections, which can result in implant loosening and device failure. Mitigating these infections is important to both implant stability and patient health. The development of antibacterial implant coatings can decrease the presence of bacterial colonies, reducing the risk for bacterial-dependent implant failure. Here, we show that electrospun polycaprolactone (PCL) fibers doped with silver nanoparticles (NPs) from a silver nitrate precursor have the potential to decrease the prevalence of Streptococcus pneumoniae while supporting osteoblast attachment and proliferation. An air plasma reduction method of PCL electrospun fibers was used to prepare fibers doped with silver NPs. Fibers were characterized using scanning electron microscopy and transmission electron microscopy for qualitative evaluation of NP distribution and quantitative analysis of fiber diameters. Antibacterial testing against S. pneumoniae was performed with successful inhibition observed after 24 h of exposure. In vitro testing was completed using Saos-2 cells and suggests that the negative surface charge has the potential to increase mammalian cell viability even in the presence of fibers containing NPs. In conclusion, this study describes a novel method to produce bioresorbable implant coatings with the ability to reduce bacterial infections surrounding the implant surface while remaining biocompatible to the host.